Marketing Strategy Analysis in Coffee Shop House of Essentials with SWOT Analysis - Suwandari, Putri Ayu; Waluyo, Minto (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Changes in people’s lifestyles in the current era of globalization can be marked by changing ways to style.. Therefore, a business must formulate a marketing strategy in accordance with existing conditions. House Of Essentials coffee shop with an industrialist and modern building concept that is comfortable for relaxing, doing assignments, and working . The aims of this research is to formulate a marketing strategy for House of Essentials using SWOT analysis. SWOT analysis is a strategy-making toolthat systematically evaluates and identifies numerous elements in order to develop a company-based strategy. based on a logic that maximizes strengths and opportunities, while minimizing weaknessesand threats in a high-stakes market. Based on the IFAS and EFAS matrix, total internal factor weighting score (strengths and weaknesses) in the IFAS matrix was 3.2857 and the external factor weighting total score (opportunities and threats) in the EFAS matrix was 2.8005. The results show that cafe House Of Essentials is in quadrant I of the matrix grand strategy, which mean cafe can adopt an aggressive strategy.